História com Dona Prizulina da beira do fogão à cultura visual - OLIVEIRA, Wolney Fernandes de (2009)
As a storytelling, this work aims at delineate new glances and senses about my own academic path and about how it is linked with other experiences shared on the imaginary that moves the daily life of my hometown. Base on the principles of autoethnography, I seek to comprehend and to rebuild part of a visual network in which some narratives gathered in Lagolândia (my hometown) are weaved, so that I can understand the role the weaving plays in the world views of its different actors. By reflecting on shared experiences about images, I propose a cartography wich defines places of memory. From these places, I show possible connections between orality, image and writing. This process I call "escrituragem". Thus, I suggestan amplification of the aesthetic universe based upon a subjective network weaved in the various daily contexts. Reality and imaginary, history and myth, all of them intertwine in one single braid, enabling new pedagogical approach es for teaching visual arts. Such process may pontentize other speheres as spaces where aesthetic, artistic and cultural knowledge may be developed.